2010
DOI: 10.1165/rcmb.2008-0275oc
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Activation Contributes to Endotoxin-Induced Diaphragmatic Dysfunction

Abstract: Calpain activation occurs in skeletal muscle in response to infection, but it is unknown if calpain inhibition improves muscle functional capacity. We hypothesized that infection induces diaphragm calpain activation, that calpain activation results in cleavage of important diaphragm cytoskeletal proteins, and that inhibition of calpain attenuates infection-induced diaphragm dysfunction. Mice (n 5 4-6/group) were given: (1) saline (intraperitoneal); (2) endotoxin (12 mg/kg intraperitoneal); (3) calpain inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 35 publications
(46 reference statements)
3
56
0
Order By: Relevance
“…Greater calpain activity leads to Z-band disintegration and myofibrillar protein breakdown (202,776), thereby depressing myofibrillar force (674). Calpain inhibitors lessen sepsis effects on muscle, reducing proteolysis (191,767) and preserving contractile function (675,685). The mechanism by which sepsis increases calpain activity is less clear.…”
Section: B Calpain Regulation In Critical Illnessmentioning
confidence: 99%
“…Greater calpain activity leads to Z-band disintegration and myofibrillar protein breakdown (202,776), thereby depressing myofibrillar force (674). Calpain inhibitors lessen sepsis effects on muscle, reducing proteolysis (191,767) and preserving contractile function (675,685). The mechanism by which sepsis increases calpain activity is less clear.…”
Section: B Calpain Regulation In Critical Illnessmentioning
confidence: 99%
“…Activation of calpains also reduces Akt phosphorylation and may therefore contribute to decreased protein synthesis [87]. Increased calpain activity decreased contractile function in septic models of muscle wasting [88,89]; thus it is possible that activation of calpains contributes to the early loss in force generation, as well as contributing to proteolysis.…”
Section: Neuropathy and Nerve Activitymentioning
confidence: 99%
“…For example, oxidative stress increases ubiquitination of cellular proteins and also activity of the UP itself [122,123]. Similarly, both calpains and caspases can be induced by free radicals [88,124,125] and free radicals have been shown to cause sarcolemmal damage, which can be reduced by inhibition of nitric oxide synthase [101]. Finally, it has also been suggested that free radicals may interact directly with the contractile apparatus of the myofilament and by modifying the protein structure, reduce contractile potential [126].…”
Section: Bioenergenetic Failure Oxidative Stress and Glycaemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overall difference in talin abundance was modest, relatively small changes in major structural proteins can lead to large changes in function. For example, Supinski and Callahan found that a 30% difference in talin abundance was associated with a 30% difference in contractile function of rat diaphragm muscle after experimental endotoxemia (33). a-actinin, a major adhesion protein found predominantly at the sarcomeric z-disk that is sensitive to calpain, was similarly altered, as assessed by immunohistology, but not by Western blotting, consistent with reports by other investigators that calpain can induce major structural changes in some proteins without degrading them (34).…”
Section: Discussionmentioning
confidence: 99%